Pendidikan Agama Islam dalam Prespektif Pendekatan Sosiologis - Mudrik Qori (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
The sociological approach is an important approach that needs to be used to maximize the contribution of Islamic Religious Education (PAI) learning, especially with regard to the horizontal dimension (habluminannas). This is at least due to the fact that the educational process itself is a social interaction, besides that, schools are also social groups or institutions. Therefore, this research was written with the aim of analyzing the role of PAI learning from the perspective of a sociological approach. In the research process, the researcher used a type of qualitative research with a library research approach, which refers to relevant reference sources. The research results show that PAI has an important role when viewed from the perspective of a sociological approach covering 3 (three) aspects, namely: individual coaching, social coaching and social interaction coaching. In the aspect of individual development, PAI's important role is to ensure that each student can grow and develop perfectly biologically (cultivating the body to grow perfectly and develop its potential) and psychologically healthy (faith, worship and morals). Then in the social aspect, PAI's important role is to encourage the creation of a harmonious family life, build a good culture, develop correct morality and foster good social values. As for the social interaction aspect, PAI's important role is to ensure good social interaction based on the values ​​of rahmatan lil alamin as basic principles in Islamic teachings.